2013
DOI: 10.1007/s11892-013-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Blood Glucose Data in Patient Education

Abstract: Many studies have tested clinical and behavioral approaches for improving glycemic control in people with diabetes. We review research to identify how blood glucose (BG) values have been used in patient-focused clinical research and interventions. We sought to describe the frequency that BG values have been the focus of patient education research and to characterize the different methods to integrate BG into an intervention, the approaches implemented to support patient education and behavior change, and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…4 Despite recommendations to incorporate problem solving as part of routine diabetes education, 3 there are gaps in services to teach and support problem solving skills. 6 Various technologies are relevant in diabetes problem solving because they provide readily available resources that can help facilitate obtaining knowledge, communicating with adults, connecting with similar others, and/or accessing feedback on blood glucose data. These efforts may facilitate adherence to the adolescent's regimen using the technologies and communication channels with which adolescents are now familiar and find acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite recommendations to incorporate problem solving as part of routine diabetes education, 3 there are gaps in services to teach and support problem solving skills. 6 Various technologies are relevant in diabetes problem solving because they provide readily available resources that can help facilitate obtaining knowledge, communicating with adults, connecting with similar others, and/or accessing feedback on blood glucose data. These efforts may facilitate adherence to the adolescent's regimen using the technologies and communication channels with which adolescents are now familiar and find acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of a color record tool in association with diabetes education to improve HbA1c has been demonstrated recently by Nishimura et al, 25 who hypothesized that color used in SMBG is helpful for patients to recognize and act on their glucose levels and demonstrated a lowering of HbA1c after 24 weeks in subjects utilizing a simple color record tool to highlight individual low or high results. A recent review by Kumah-Crystal and Mulvaney 26 indicated a need to improve and expand support for people with diabetes in their daily use of glucose values to maintain and improve glycemic control. Subject responses in our current study support the utility of a meter-based CRI to facilitate improved awareness of glucose ranges and provide easier interpretation of readings and the potential to make it easier to report in or out of range results to their HCP.…”
Section: Discussionmentioning
confidence: 99%
“…In general, surveys show that in most studies, internet intervention has been mainly used to transfer blood glucose data and other patient information to physicians and to use feedback on their health status [81,82]. Web-based learning is a tool for continuing education to increase the number and skills of health workers and patients.…”
Section: Internetmentioning
confidence: 99%